BOOK REVIEW: IULIA ANDREEA MILICĂ, “THE SOUTH IN NINETEENTH CENTURY AMERICAN FICTION”, IAȘI, VASILIANA ‘98, 2014, 373P. - PRECUP, Amelia (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Iulia Andreea Milică has already made a name as a specialist on the culture and literature of the American South. The author’s assiduous scholarly efforts to present the complexity of this regional literary culture beyond the popular clichés have enriched the contribution of Romanian scholars to the field of American literary studies. Iulia Andreea Milică’s interest in the American South began with her doctoral research, published as Southern Cultural Dimensions in Flannery O’Connor’s Fiction. Her contribution later materialized in several books and articles on Southern writers such as William Faulkner, Ellen Glasgow, or Katherine Anne Porter. In her 2013 book Literary Representations of the Southern Plantation, Iulia Andreea Milică supports the inclusion of the founders of the plantation romance in the discourse on the evolution of American literature. Although the scope of her other book on American literature, namely Studies in American Literature (2013), is wider, Milică’s interest in the American South is still very clear in her analyses of Southern identity. The reader under review, The South in Nineteenth Century American Fiction, falls into the same category of valuable resources for students and scholars interested in the literary representations and representatives of the nineteenth-century American South.